2022
DOI: 10.3390/aerospace9010036
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Design, Analysis and Validation of a Small Blended-Wing-Body Unmanned Aerial Vehicle

Abstract: This paper describes the aerodynamic design and assessment of a blended-wing–body (BWB) configuration under the distributed electric propulsion (DEP) installation constraints. The aerodynamic design rationale and process is described, as well as how the DEP system is considered and simplified in the optimization design process. Both the BWB configuration and the DEP induced effects are numerically simulated and analyzed using the Reynolds Averaged Navier–Stokes (RANS) computational fluid dynamics (CFD) flow so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…where AR ≈ 3 for the delta wing aircraft. Using the value of the aspect ratio in Equation ( 4), C Lα = 3.78 rads, which is similar to what is reported by Wang et al [30]. Additionally,…”
Section: Dynamic Modellingsupporting
confidence: 86%
“…where AR ≈ 3 for the delta wing aircraft. Using the value of the aspect ratio in Equation ( 4), C Lα = 3.78 rads, which is similar to what is reported by Wang et al [30]. Additionally,…”
Section: Dynamic Modellingsupporting
confidence: 86%
“…The design of a trim distributed electric propulsion-based blended wing body configuration by CFD simulation and Wind tunnel testing to evaluate the design quality and obtained the lift-to-drag ratio of 22.31 at an angle of attack of 4°. The cruise condition's pitching moment and static margin met the required design requirements (Wang & Zhou, 2022). The design of agricultural use of unmanned aerial vehicles concluded that the UAVs did not require a separate navigation station and airport since they could be landed on the edge of the agricultural land.…”
Section: Introductionmentioning
confidence: 94%